Salmonella enterica serovar Panama meningitis in exclusive breastfeeding infants: Report of 4 cases, clinical features and therapeutic challenges. Issue 19 (May 2017) - Elenga, Narcisse; Cuadro, Emma; Long, Laurence; Njuieyon, Falucar; Martin, Elise; Kom-Tchameni, Rémi; Defo, Antoine; Razafindrakoto, Sitraka H.; Mrsic, Yajaira; Henaff, Fanny; Mahamat, Aba
Abstract: Rationale: The pathway of Nontyphoid Salmonella meningitis, especially in exclusive breastfeeding infants, has not been well characterized. Patient concerns: We analyzed data related to nontyphoid Salmonella meningitis in 4 infants. Diagnoses: No diarrhea was observed and the coproculture was negative for all patients. Interventions: Early diagnosis and treatment with combination of third-generation cephalosporins plus quinolones for a minimum of 3 weeks is necessary to avoid severe sequelae and death. Outcomes: The first 3 patients had a good evolution, whereas the last patient had multiple brain abscesses and hydrocephalus requiring treatment with a ventriculoperitoneal shunt. Lessons: The highlights of our study are that all infants were exclusively breastfed, no diarrhea observed and the negative coproculture for all the 4 patients, which is relatively rare for Salmonella infection.